Development of Bilingual Mathematics Digital Pocket Book to Improve Student’s Ability in Understanding Plane Topic - Nadya Ramadhani; Rahman Pratama Hasibuan (MultiTech Publisher, 2023)
The aim of this study was to develop a valid, practical, and effective bilingual mathematics digital pocket book to improve students’ ability in understanding plane topic. The study was held at SMP Islam Al-Ulum Terpadu Medan. The subject of this research was class VII-A. This study was a research and development (R&D) study using the ADDIE Model. The data collection technique used a questionnaire sheet for the assessment of material experts, teaching materials experts, learning practitioners and student responses. The results showed that the bilingual mathematics digital pocket book in plane topic obtained an average percentage of 93.18% with the criteria